1994
DOI: 10.1007/bf00357567
|View full text |Cite
|
Sign up to set email alerts
|

Microbial flora and some chemical properties of ersho, a starter for teff (Eragrostis tef) fermentation

Abstract: Ersho is a clear, yellow liquid that accumulates on the surface of fermenting teff-flour batter and is collected to serve as an inoculum for the next fermentation. The pH of ersho samples was about 3.5 and titratable acidity ranged between 3.1% and 5.7%. The mean aerobic mesophilic counts from four households varied between 6.9×10(6) and 1.3×10(8) c.f.u./ml and the aerobic bacterial flora consisted of Bacillus spp. Mean yeast counts ranged between 5.2×10(5) and 1.8×10(6) c.f.u./ml and comprised, in order of ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

1995
1995
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 5 publications
2
13
0
Order By: Relevance
“…In this study, we investigated the overall yeast diversity in indigenous fermented foods and beverages of Ethiopia. We identified much more yeast species than reports in previous studies on fermented foods from Ethiopia and other African countries . The remarkable variation of yeast cell counts and species distribution in different types of Ethiopian fermented foods and beverages assessed, and even within the same types of the fermented products observed in this study could be explained by the diversity in food composition, fermentation processes, duration of fermentation, and storage and handling practices of the Ethiopian traditional fermented products.…”
Section: Discussionsupporting
confidence: 42%
“…In this study, we investigated the overall yeast diversity in indigenous fermented foods and beverages of Ethiopia. We identified much more yeast species than reports in previous studies on fermented foods from Ethiopia and other African countries . The remarkable variation of yeast cell counts and species distribution in different types of Ethiopian fermented foods and beverages assessed, and even within the same types of the fermented products observed in this study could be explained by the diversity in food composition, fermentation processes, duration of fermentation, and storage and handling practices of the Ethiopian traditional fermented products.…”
Section: Discussionsupporting
confidence: 42%
“…From 249 isolates 24 isolates were selected on the basis of their acid production potential. As Ashenafi [ 8 ], indicated, lactic acid bacteria were responsible for the acidic characteristics of the dough and reduced the pH to about 4.7 and were selected for molecular identification. Lactic acid bacteria produced acid at 12h of incubation.…”
Section: Resultsmentioning
confidence: 99%
“…In this study Lactobacillus paracasei, Enterococcus durans, Enterococcus hirae, Enterococcus avium, Lactobacillus brevis, Enterococcus faecium, and Bacillus subtilis were also identified from fermenting teff dough. Different workers indicated that microbial flora of fermenting teff dough were complex and shown to include Enterobacteriaceae and aerobic mesophilic bacteria [ 8 ], aerobic spore formers, and lactic acid bacteria [ 7 – 9 ]. Brhanu et al [ 9 ] have indicated that the microbes were involved in teff flour, indicating that there is the involvement of mold, Enterobacteriaceae, aerobic mesophilic bacteria, yeasts, fermentative aerogenic, Gram negative bacteria rods, lactic acid bacteria, and Bacillus spp.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other microorganisms as Enterobacteriaceae, yeasts and mould were isolated in a lot of based-cereals fermented foods and can influence their quality (Ashenahi, 1994).…”
Section: Introductionmentioning
confidence: 99%